(untitled) (Impetus, 2025)
The purpose of this study was to analyze the effects of cooperative games on physical and verbal aggression and self-esteem in a group of elementary school students in physical education classes, using the Agression Questionnaire and TAE-Student instruments. Twenty fifth-grade students from Campus B of the Ciudadela Educativa del Magdalena Medio institution participated. Significant differences were found in physical and verbal aggression levels before and after the pedagogical intervention, but no changes were observed in self-esteem levels. Significant gender differences were also found; verbal aggression predominated among girls, while boys presented high levels of physical aggression. The results suggest the need to increase the use of these types of cooperative game-based interventions at all levels of schooling, as they could positively impact aggression levels.